Environmental sustainability orientation and corporate social responsibility influence on environmental performance of small and medium enterprises: The mediating effect of green capability. (9th May 2022) - Rehman, Shafique Ur; Bresciani, Stefano; Yahiaoui, Dorra; Giacosa, Elisa
Abstract: Despite the increasing research to determine the influence of environmental sustainability orientation (ESO) and corporate social responsibility (CSR) on environmental performance, our understanding is to see the mediating effect of green capability between ESO, CSR, and environmental performance is lacking. Data were collected by using survey questionnaires from top management of the construction and manufacturing industry in Malaysia. A total of 377 questionnaires become part of the final analysis. The researchers used SmartPLS 3.2.8 and SPSS 25.0 for analysis. The structural equation modeling (SEM) was followed to determine the variables validity and path relationships. The findings elucidate that ESO and green capability are significantly associated with environmental performance. In contrast, CSR has no direct influence on environmental performance. Moreover, ESO and CSR significantly influence green capability. Green capability mediates between ESO, CSR, and environmental performance.